Is trade liberalization a solution to the unemployment problem? - Yanikkaya, Halit (2018)
This paper examines how trade liberalization affects the growth rate of sectoral employment in developed and developing countries. The estimation results imply that trade openness in the form of higher trade volumes has not been successful in generating jobs in developing countries. The overall weak, negative employment response to trade volumes may be explained by the negative output response to trade openness in these countries. Our estimates also indicate that higher trade volumes have adverse effect on industrial employment in developed countries. Moreover, while they have positive effect on employment in industry and services in developing countries, trade barriers have adverse effect on employment growth in services for developed countries. Our overall results imply that while trade barriers have relatively little adverse effects and/or in some case a positive effect on employment both in developing and developed countries, higher trade volumes have an adverse effect on industrial employment in developed economies. Thus, trade openness is not in itself a solution to the unemployment problems of developing countries and yet it has not been the prime factor to blame for the lower employment levels in developed countries.